Cytotoxic and antiproliferative activity of a fucoidan-rich extract from Lessonia trabeculata on 4T1 murine mammary adenocarcinoma cells - Toccas-Salas, Mary (2023)
Neoplastic tumors are characterized by invasiveness and metastasis.  Neoplasticcells are genetically heterogeneous and can develop resistance to chemotherapeutic agents. For this reason, plants continue to be an important source of new anticancer products. Objective. To determine the cytotoxic and antiproliferative activity of a fucoidan-rich extract of native Lessonia trabeculata (EFLt) on the tripe negative murine mammary adenocarcinoma cell line 4T1. Methods. Cytotoxicity and IC50 were determined in 4T1 monolayers using the MTT reagent. To demonstrate antiproliferative activity, “wound” closure and anticlonogenic methods were applied using the IC50 of EFLt and Doc (doxorubicin). “Wound” closure was evaluated by discrete times sweep to determine percentage inhibition of cell migration; the anticlonogenic effect was evaluated by colony counting 7 days after treatment and the survival fraction was determined. In addition, cytotoxicity and antiproliferative activity were evaluated by combining the IC50 of EFLt and Dox. Percent migration and colony counts were performed using ImageJ software. Results. The IC50 (950 μg/mL) of EFLt was 56% cytotoxicity, 80,3% inhibition of cell migration, 68% inhibition of colony formation.The IC50 of Dox was 0,5 μg/mL. Conclusions. EFLt exerts concentration-dependent cytotoxicity and antiproliferative effect on 4T1. Further studies in more complex models are needed to elucidate the anti-tumor potential of EFLt.